Inovasi Manajemen Sumber Daya Manusia Berbasis Prinsip Islami: Analisis pada Lembaga Pendidikan Islam di Thailand - Fadhillah, Rini; Hayati, Isra (Hikmah, 2023)
Human resources are one of the most important aspects of managing an educational institution. Western theory demands innovations that are sometimes incompatible with Islamic nature. In this regard, this study aims to analyze human resource management innovations based on Islamic principles at Sangkhom Islam Wittaya School Thailand. This research uses case study-based qualitative research methods. Data collection techniques used observation, interviews and documentation studies. The research informants consisted of principals, educators and education personnel. The results found that human resource management is carried out inclusively by applying Islamic principles, namely regardless of background, identity, and treated fairly, valued, and have equal opportunities in terms of recruitment, development, promotion, and performance appraisal. The school's preference for Islamic ideology and the enhancement of Islamic knowledge are taken into consideration in the placement of human resources. Human resource performance is assessed from a sense of responsibility to carry out the mandate, the profession, and a sense of moral responsibility. The main obstacles in managing human resources are finance and developing the quality of teachers. The results of this study are recommended for Islamic educational institutions that strive to develop the quality of educators and education personnel.